Ethical use of Artificial Intelligence in Research Publications: A collective responsibility - Muhammad Ajmal Chaudhary (Journal of the Pakistan Medical Association, 2026)
“Artificial intelligence is not a substitute for human intelligence; it is a tool to amplify human creativity and ingenuity.”— Fei-Fei Li The rapid integration and transformation1,2 of Artificial Intelligence (AI) such as ChatGPT (Generative Pre-trained Transformer) into medical research2 necessitates clear guidelines to provide a framework for researchers, authors, reviewers and editors. Through transparent reporting, rigorous evaluation3 and a commitment to open science, we aim to advance knowledge and innovation in AI while upholding the highest standards of integrity, equity and ethical conduct. This increasing use of generative AI in academic publications necessitates timely and thoughtful policy reforms that carefully align technological advancements with the principles of scholarly integrity. Journals have a central role in guiding this transition by establishing AI policies that are transparent, enforceable, and firmly grounded in ethical standards.